Psychosocial risk factors in the work environment - Khroufa, Ghania (Journal of Human Sciences, 2022)
Of course, in the workplace, not everything works perfectly, however if many psychosocial risk factors accumulate, workers may begin to feel discouraged and unmotivated. These factors involve those conditions in the workplace that can harm the health of workers and thus cause stress for them, and not only that, their long-term effects can lead to illness. Therefore, and our desire, we will try to shed light on the psychological and social risk factors in the work environment to know their impact on the worker’s behavior and the level of his performance in his work environment.